Method validation of heavy metal analysis of lead in Oyster (Crassostrea iradelei, Faustino, 1932) flesh by flame atomic absorption spectroscopy - Eola, Azl Rose D.
Crassostrea iredalei (Faustino, 1932), also known as Slipper-cupped oyster, is one of the popular seafood commodities in the Philippines. As bivalves, they have higher abilities to accumulate metals, such as lead. Lead like most heavy metals are not usually eliminated by natural processes in the marine ecosystem, thus accumulate in the sediments and enter the biological systems of plants and animals. In consequence, different parameters in method validation are done on the heavy metal analysis of this species of oyster to assess the performance of the method and determine its limitations. Moreover, the level of Pb in Crassostrea iredalei was assessed to confirm its safety for human consumption. The sample had a Pb concentration with the range of 1.43 ± 0.53 ppm which is lower than the maximum level of Pb allowed for a shellfish product in the Philippines by the FDA. The LOD and LOQ of the instrument were 0.1185 ppm and 0.3951 ppm, respectively. While the LOD and LOQ of the method were found to be 0.0946 ppm and 0.3153 ppm, respectively. The validated method was linear over the concentration ranges of 0-2 mg/L Pb. The coefficient of determination (R2) obtained from the linear regression is 0.997. the relative spike recovery was 72.4% and high values of repeatability precision were obtained. The validation parameters proved the sensitivity of the instrument and method to the analyte. The repeatability precision obtained was 36.97% relative standard deviation. However, this gave an inconclusive result since the RSD values obtained are greater than the AOAC accepted value.